(untitled) (Applied Biological Research, 2017)
The study was aimed to find the reaction of a major insect pest of stored paddy viz., Angoumois grain moth Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) to different indigenous aromatic paddy varieties. The grains of 11 paddy varieties commonly grown in Terai region of West Bengal (India) were evaluated in May-September in 2011 and 2012. The results showed that the insect completed four generations during the period. The favourable season for the development of S. cerealella was May July when it takes only 29.17-35.21 days to complete the generation. The insect development was significantly fast in paddy variety ‘Gobindobhog’, ‘Kolajoha-small’ and ‘Mohanbhog’ (33.33, 34.35 and 34.59 days) and caused higher damage to grain number (5.05-6.51%) and weight (3.76- 4.44%). The insect development was prolonged in paddy cv. ‘Tulaipanji’ (36.23 days) with less damage to grain number (2.99%) and weight (1.98%). All the developmental stages showed significantly negative relation with temperature but significant positive relation with relative humidity.